Julián de Toledo y la realeza visigoda - García Herrero, Gregorio (Antigüedad y Cristianismo, 1991)
A detailed examination of the terms used to describe the kingship and its caracteristics reveal the evolution of the concepts related to this subject that has taken place in the ideology of Julian, and also the distinctive feature introduced by the Historia Wambae, example of a particular genre. The Wambana royalty is now considered to be the substitute and heir of the Hebrew Veterotestamentaria Monarchy rather then than legataria of the Imperial authority. Dispersed and practically vanished from sight, except for a few lines of pure erudition, the Historia Wambae should be considered as a creation worthy of imitation, written with a political purpose not as evident as has been traditionally alledged.